2019
DOI: 10.1111/jfpp.14288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound‐assisted blanching on the processing and quality parameters of freeze‐dried guava slices

Abstract: In this work, ultrasound‐assisted blanching (UAB) has been applied to study its effect on different physical and chemical characteristics and the total process time (TPT) of freeze‐dried guava slices (DGS). Additionally, the process energy consumption was estimated, and the overall process was modeled. UAB was applied at 5‐ and 10‐min exposure times and at 65°C to evaluate the polyphenol oxidase (PPO) and peroxidase (POD) activities. Then, guava slices were freeze‐dried and the TPT with and without UAB were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Chandra et al's (2021) pretreatment study confirms that a pretreatment prior to drying is essential for the retention of polyphenols. On the contrary, ultrasound‐assisted blanched and freeze‐dried guava slices showed 13.73 ± 1.75% and 28.47 ± 0.48% reduction in phenolics on 5‐ and 10‐min ultrasound treatment, respectively (Alvarez et al, 2019).…”
Section: Effect Of Drying Methods On the Retention Of Total Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chandra et al's (2021) pretreatment study confirms that a pretreatment prior to drying is essential for the retention of polyphenols. On the contrary, ultrasound‐assisted blanched and freeze‐dried guava slices showed 13.73 ± 1.75% and 28.47 ± 0.48% reduction in phenolics on 5‐ and 10‐min ultrasound treatment, respectively (Alvarez et al, 2019).…”
Section: Effect Of Drying Methods On the Retention Of Total Phenolicsmentioning
confidence: 99%
“…The antioxidants loss is attributed to several factors, such as drying time, thermal degradation, level of phenolic compounds, enzyme activity, and Maillard browning (Siow & Hui, 2013). Increased length of exposure of ultrasound for blanching before freeze‐drying guava slices boosts AA (Alvarez et al, 2019). Ultrasound‐aided osmotically dehydrated papaya slices demonstrated increased DPPH radical scavenging activity than untreated papaya slices, similar to the TPC trend.…”
Section: Effect Of Drying Methods On the Retention Of Antioxidant Act...mentioning
confidence: 99%
“…Importantly, they observed that drying time was reduced by about 30% for blanched fruits. Another group of authors [26] studied the influence of ultrasound (US)-assisted blanching on the FD process in guava. They proved that such kind of pretreatments reduced, to a large extent, the peroxidase activity and, to a lower extent, the polyphenol oxidase activity.…”
Section: Blanchingmentioning
confidence: 99%
“…The reduction in FD costs with high-quality products is still considered a challenge. However, adequate food pretreatment can significantly decrease the energy consumption associated with FD [25][26][27] and improve the quality of dried food [28,29]. FD allows obtaining products of very good quality, with a low final moisture content of 1-4% [5].…”
Section: Introductionmentioning
confidence: 99%
“…To improve processes, new methods and technologies have been proposed for enhancing heat exchange while reducing energy losses. Ultrasound (US) is a promising non-thermal food processing technology which has been recognized as an effective tool for intensifying heat transfer in different processes such as air drying, cooling, freezing, and blanching, increasing the efficiency of the processes while improving the quality of the final product [20] , [11] , [33] , [1] , [43] , [37] , [36] .…”
Section: Introductionmentioning
confidence: 99%